Aquatic insects: a review study for some biological and environmental aspects in Shatt Al- Arab and Southern Marshes of Iraq - Ahmed, Huda Kadhim (Iraqi Journal of Aquaculture, 2021)
Several studies have been conducted on aquatic insects in southern Iraq that included various taxonomic, biological and ecological aspects of the larval and adult stages in aquatic environments, which reflects their abundance and important role in the societies and ecosystems inhabited by them. They serve as adequate food for groups of predatory vertebrates and invertebrates. The studies included the environments of the Shatt al-Arab River and its branches, temporary and permanent ponds emanating from them, as well as some areas of the marshes. Aquatic insects play an important nutritional role, as many types of fish depend on them and form an important link for energy transfer from the bottom to the top in the food web because many types of them show a wide difference in their feeding habitats, so their importance lies in the interconnected ecosystems in creating an ecological balance within the rings of the food chain. The ability of aquatic insects to increase their reproduction rates make them excellent model for analyzing the structure and function of the freshwater ecosystem. Some of their species that spend part of their life in water have been used as ecological indicators in determining the state of aquatic environments and estimating environmental risks as they are greatly affected by the state of the environment in which they live. It is one of the most affected individuals in terms of surface water pollution.